Estimating the Costs of Issuer-Paid Credit Ratings - Cornaggia, Jess; Cornaggia, Kimberly J. (Review of Financial Studies, 2013)
We compare the stability and timeliness of credit ratings produced by a traditional issuer-paid rating agency (Moody's Investors Service) and a subscriber-paid rater (Rapid Ratings). Moody's ratings exhibit less volatility but are slower to identify default risk. We control for Moody's aversion to ratings volatility and still find its ratings lag Rapid Ratings'. More importantly, accuracy ratios indicate that Rapid Ratings provides a better ordinal ranking of credit risk. We quantify the loss avoidance associated with Rapid Ratings'signals to estimate costs associated with regulatory and contractual systems based on issuer-paid ratings.